A new species of Dandya (Alliaceae) from the Balsas River Basin, Mexico - Lopez-Ferrari, Ana Rosa; Espejo Serna, Adolfo (Instituto de Ecología, A.C., 1992)
Dandya balsensis López-Ferrari & Espejo is described as new to science. It appears to be related to Dandya thadhowardii Lenz. Comments are made about the history and distribution of the species of Dandya and a key for their identification is given.